The Economy of the Arctic in the Modern Coordinate System - V. A. Kryukov; Yu. V. Kryukov (Контуры глобальных трансформаций: политика, экономика, право, 2019)
The article deals with modern features of the Arctic economy. It is shown that in those spheres and directions of economic activity, which are associated with the development of natural resources (primarily mineral resources) and focused on obtaining returns on investment, there is a strengthening of the role not only of new knowledge and new technologies, but also significantly increase the role and importance of forms of cooperation of the parties involved in the implementation of projects. This approach allows, on the one hand, to solve the problem of attracting investment in high-risk and, at the same time, high-yield projects, but it also will not allow to fully realize the opportunities associated with the development and use of domestic research and production potential in the implementation of projects in the framework of such “hybrid forms”. One of the direct and immediate consequences of this approach in the practice of field development in the Arctic zone of the Russian Federation (AZRF) is a significant increase in the knowledge-intensive service sector, which meets the needs for equipment and labor by borrowing foreign advanced technologies and the widespread use of interregional watch. These processes lead, in particular, to the fragmentation of the economic space of the country (reducing the degree of connectivity of the economies of different regions), as well as to the stagnation and extinction of urbanized settlements in the Russian Federation.